Peat Soil As Natural Adsorbent To Reduce Ammonium In Palm Oil Mill Effluent (POME) - Fariha Najwa, Azahar (2023)
The presence of ammonia (NH3) which are emitted from palm oil mill effluent (POME) cause a highly unpleasant odour to the surrounding areas. NH3 produced by anaerobic bacteria are emitted when POME is treated via anaerobic digestion. Therefore, concentrations of NH3 need to be reduced for abatement of odour and health control. An investigation using modified peat soil as natural adsorbent by chemical activation using sodium hydroxide (NaOH) was carried out to study the characteristics and determine its suitability as a new adsorbent with its effect on the removal efficiency of ammonium produced by POME. Numerous studies have proved that peat soil potentially be useful as adsorbent in an aerobic condition due to contain high carbon content and pores. Result shows of NaOH were obtained from the ammonia test by 30 min of contact time, 100 rpm of agitation speed and 9 g of dosage adsorbent with value of 85%. Meanwhile for ratio 1:3 of NaOH activation, the result obtained by 90 min of contact time, 50 rpm of agitation speed and 9 g of dosage of adsorbent with value of 79%. The Scanning Electron Microscope (SEM) images of modified peat soil that activation by NaOH showed more porous space structure and create larger voids. While, the Fourier-transform Infrared (FTIR) demonstrated the different functional of the raw peat soil and modified peat soil. In this regard, the modified peat soil by NaOH activation can create a new industry for application in NH3 and odour removal, thus can protect the environment from odour pollution.